Associação entre o consumo alimentar e a síndrome de dumping de pacientes bariátricos no contexto da pandemia de COVID-19 no Brasil. - CUNHA, Samantha Cecilia Vera Cruz da (2024)
Introduction: Bariatric surgery is one of the most effective, safe and indicated interventions for the treatment of obesity. However, despite its benefits, this procedure can cause unwanted complications such as dumping syndrome. In addition, the covid-19 pandemic interfered with the routine of individuals, impacting the health and eating habits of the population, including bariatric patients. Objectives: To analyze the association between food consumption and dumping syndrome in bariatric patients in the context of the Covid-19 pandemic. Materials and Methods: This is a cross-sectional, descriptive, analytical, online study with bariatric patients over 18 years old, in the context of the Covid-19 pandemic, data collection was carried out through the application of forms available remotely. Results: The study was carried out with 412 participants, most of them female, with high school education, monthly family income above seven quarters minimum and with more than three years of surgery. A high consumption of fresh foods was observed, however, at the same time there was a high consumption of ultra-processed foods, in addition to the prevalence of dumping symptoms in the consumption of ultra-processed foods. Conclusion: Dumping syndrome was highly prevalent in bariatric patients, especially in individuals who consume ultra-processed foods. In addition to the composition of food, the symptoms imply eating habits. Finally, the importance of nutritional monitoring for this public is evident.